Effects of Restrained, External, and Emotional Eating Styles on Weight Gain Among Female Students at Faculty of Public Health, Universitas Indonesia - Muharrani, Nindhita Priscillia; Achmad, Engkus Kusdinar; Sudiarti, Trini (KnE Life Sciences, 2018)
ABSTRACT: Continuous weight gain increases the risk of coronary heart disease. This research was a six-week prospective cohort study aimed at identifying the effects of restrained, external, and emotional eating styles on weight gain by controlling energy intake, physical activity, and socioeconomic status. A total of 40 female students were assessed at three points within a six-week period. Eating styles were assessed using a self-administered questionnaire based on restrained, externality, and psychosomatic theories. There was a significant weight gain of 0.32 kg on average among female students. Twenty-five percent of respondents experienced changes in eating style, while the rest were consistent with one eating style. A significant effect on weight gain was found only in external eating before and after being controlled by energy intake (p<0.05). This indicates that external eating, rather than emotional eating and restrained eating, drives weight gain among female college students. This study also found that the proportion of restrained eating was higher in students with normal weight than in those who were overweight, whereas emotional eating was higher in underweight students than overweight students, and external eating was higher in underweight students than obese students. In conclusion, external eating may cause weight gain, yet restrained and emotional eating are not necessarily effective ways to control weight either. Therapies to stop the weight gain epidemic are urgently needed.